A Scoping Review on Malaria Prevention and Control Intervention in Fragile and Conflict-Affected States (FCAS): A Need for Renewed Focus to Enhance International Cooperation - Sanjay Pattanshetty; Viola Savy Dsouza; Anupama Shekharappa; Maheswara Yagantigari; Rohit Raj; Aniruddha Inamdar; Issam Alsamara; Harsh Rajvanshi; Helmut Brand (Springer, 2024)
Abstract Malaria is a major public health problem in developing countries. The burden of malaria in fragile and conflict-affected states (FCAS) is increasing year by year. Moreover, the population living in FCAS is often the most vulnerable and at high risk of malaria due to factors, such as deteriorating healthcare system, mass relocations, and reduced resilience to shocks. Therefore, this scoping review aims to map the interventions that are conducted at the FCAS on malaria prevention among the general population. In addition, this review can help policy-makers and international health bodies, providing a comprehensive overview that can lead to more targeted, effective, and context-specific interventions. Databases, such as PubMed, EBSCO-CINAHL, Web of Science, ProQuest, and Cochrane Central Register of Controlled Trials, were searched using specified search terms. A total of 3601 studies were retrieved from the search. After screening, 62 studies were included in the synthesis that met the eligibility criteria. Narrative analysis of the findings was done. The results revealed that in fragile countries, interventions for children below 5 years of age included IPTi, TDA, and ACT. In conflicted countries, interventions for children below 5 years of age included TDA, LLINs, SMC, drug trials, and vaccination. Similar interventions were reported for other age groups and populations. Despite ongoing conflicts, malaria interventions have been maintained in these countries, but a persistent high burden of malaria remains. To achieve the goals of malaria elimination, the results of the review highlight the need for continued research and evaluation of malaria control interventions to assess their effectiveness and impact. Strengthening health systems, building partnerships, utilizing digital health technologies, and conducting context-specific research are recommended to improve healthcare access and reduce the burden of malaria in FCAS.